PERAN MEDIASI KEPUASAN KOMUNIKASI DAN ANTESEDEN KINERJA KARYAWAN - Purnama Yanti Purba (Riset Manajemen dan Akuntansi, 2016)
The purpose this study is to examine the effect of communication practice on job satisfaction and organizational commitment mediated by communication satisfaction and to know the effect of job satisfaction and organizational commitment on job performance in the field of education services, Ganesha Operation in Surakarta and Karanganyar. The existence of previous research that found the fully mediated of communication satisfaction on communication practices toward job satisfaction and organizational commitment, and also the recommendation of the previous research motivate researcher to conduct this study. Samples taken were 100 employees of Ganesha Operation in Surakarta, and Karanganyar. Sampling technique of this study is proportional random sampling method. The statistical methods used to test the validity, reliability, and the research hypothesis is regression analysis of Baron and Kenny (1986) and multiple regression analysis. Results of this study indicate that communication practices have a positive effect on communication satisfaction, job satisfaction, and organizational commitment. The effect of communication practices toward job satisfaction, and organizational commitment were fully mediated by communication satisfaction. In addition job satisfaction and organizational commitment have a positive effect on job performance. Keywords: Communication practices, communication satisfaction, job satisfaction, organizational commitment, and job performance